Activation of Akt by SC79 decreased cerebral infarct in early cerebral ischemia-reperfusion despite increased BBB disruption. (10th August 2018) - Liu, Xia; Kiss, Geza K.; Mellender, Scott J.; Weiss, Harvey R.; Chi, Oak Z.
Highlights: SC79 is a selective and potent Akt activator and permeable to cell and BBB. SC79 decreased the size of cortical infarct in early cerebral ischemia-reperfusion. Early activation of Akt may be vital for neuronal survival in ischemia-reperfusion. SC79 increased BBB permeability in ischemic-reperfused and in control cortex. The decrease in the size of infarct may be related to non-BBB effects of SC79. Abstract: Activation of Akt has been suggested to produce neuronal protection in cerebral ischemia. Decreasing blood-brain barrier (BBB) disruption has been associated with a better neuronal outcome in cerebral ischemia. We hypothesized that activation of Akt would decrease BBB disruption and contribute to decreasing the size of infarct in the early stage of cerebral ischemia-reperfusion within the therapeutic window. Transient middle cerebral artery occlusion (MCAO) was performed in rats under isoflurane anesthesia with controlled ventilation. Rats were treated with SC79 (a selective Akt activator which is cell and BBB permeable) 0.05 mg/kg × 3 i.p. or vehicle i.p. perioperatively. After one hour of MCAO and two hours of reperfusion, the transfer coefficient (Ki ) of 14 C-α-aminoisobutyric acid ( 14 C-AIB, molecular weight 104 Da) and the volume of 3 H-dextran (molecular weight 70, 000 Da) distribution were determined to measure the degree of BBB disruption. At the same time point, the size of infarction was determined using tetrazolium staining. In an additional group of rats, a higher dose of SC79 (0.5 mg/kg × 3) was administered to determine the size of infarct. Administration of SC79 increased the Ki in the ischemic-reperfused cortex (IR-C, +32%, p <  0.05) as well as in the contralateral cortex (CC, +35%, p <  0.05) when compared with the untreated animals with MCAO/reperfusion. The volume of dextran distribution was not significantly changed by SC79. SC79 treatment significantly produced a decrease in the percentage of cortical infarct out of total cortical area (12.7 ± 1.7% vs 6.9 ± 0.9%, p <  0.001). Increasing the dose of SC79 by ten times did not significantly affect the size of cortical infarct. Contrary to our hypothesis, our data demonstrated that SC79 decreased the size of the infarct in the ischemic-reperfused cortex despite an increase in BBB disruption. Our data suggest the importance of activation of Akt for neuronal survival in the early stage of cerebral ischemia-reperfusion within the therapeutic window and that the mechanism of neuroprotection may not be related to the BBB effects of SC79.